Using augmented reality and location-awareness to enhance visitor experience: A case study of a theme park app - Chan, C. M.; Lau, Sian Lun * (2020)
Mobile travel has become a significant trend due to the emergence of smartphones and mobile technology. Existing researches show that the integration of location-based services (LBS) is potentially adding significant values to the mobile tourism industry. The purpose of this study is to develop a location-based mobile application for theme park visitors to enhance their visiting experience. The application of location based solutions such as interactive map, push notification services with geo fencing and augmented reality tour guide will be involved in this study. Google Map SDK for Android, Google ARCore Sceneform, GeoFire and SQLite methodology is adopted to build the application. An online survey is conducted to evaluate the user acceptance for the mobile application by sending Android Package Kit (APK) to the users. The result shows that majority of respondents had positive attitude towards the application and agreed that the application will enhance their park visiting experience. The conclusion can be drawn that the application can be further improved with features which contributes to the digitalization of outdoor parks or other fields in mobile tourism.